Pengenalan Publikasi Ilmiah Bagi Mahasiswa Pgsd Universitas Pgri Ronggolawe Melalui Literasi Teknologi Pada Mata Kuliah Bahasa Indonesia - Pujiastuti, Arik Umi (JURNAL PENDIDIKAN DASAR NUSANTARA, 2022)
The aim of this study is to describe the ability to identify scientific publications through technological literacy including, the ability to access scientific articles, select scientific articles, and develop scientific articles that have 76 class PGSD, class of 2018. This kind of study is a class action study. The data collection used is a questionnaire for data ability to access and select scientific articles, while the documentation techniques for data ability to compile the scientific article so, data analysis USES a quantitative descriptive technique. Research shows that, while the ability to access scientific articles before Indonesian subjects, 201% of students understand how to access scientific journals while 79.9% do not understand access to them and that percentage is equal to the ability to access scientific articles. 16.3% understand the menu in scientific journals while 83.7% do not understand the journal’s menu, 29.6% understand how to keep journal links where as 70. 4% do not understand an increase occurred 100% after technology-literacy breeding in Indonesian subjects. Studies of the ability to select a scientific article before Indonesian subjects are: 100% PGSD students cannot distinguish between research and non-research artists do not use science as referral for college work, and use referrals from sites other than scientific journals and after the technology-literacy experience of an Indonesian course there is a 100% increase. Next, the science where 20 students score 72, 19 score 70, 14 students score 7, 12 students score 73, 3 score 75, 3 more with 78, 2 score 76 and 2 score 77, and 1 student scores 69.